2009
DOI: 10.1074/jbc.m109.016444
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Cofilin-1 in Regulating Thrombin-induced RelA/p65 Nuclear Translocation and Intercellular Adhesion Molecule 1 (ICAM-1) Expression in Endothelial Cells

Abstract: The nuclear factor B (NF-B)2 represents a ubiquitously expressed family of transcription factor participating in various biological effects ranging from immune, inflammatory, and stress-induced responses to cell fate decisions such as proliferation, differentiation, apoptosis, and tumorigenesis (1, 2). The mammalian NF-B family is comprised of five members: RelA (p65), RelB, c-Rel, NF-B1 (p50 and its precursor p105), and NF-B2 (p52 and its precursor p100). A characteristic feature of these proteins is the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 61 publications
9
65
1
Order By: Relevance
“…Given the involvement of Pyk2 and its downstream kinase c-Src in activating RhoA/ ROCK pathway (19,45,46), it is possible that Pyk2 promotes nuclear translocation and, consequently, DNA binding of RelA/ p65 by causing alterations in the actin cytoskeleton. Consistent with this possibility, inhibition of Pyk2 by tyrphostin A9 attenuates thrombin-induced Ser3 phosphorylation and, thereby, inactivation of cofilin1 (K.M.B., unpublished results), an actin-binding protein that occupies a central position in Rho-actin pathway mediating RelA/p65 nuclear translocation (43). However, in view of the reports that Pyk2 can also function downstream of RhoA/ROCK (47,48), the other possibility that RhoA/ROCK engages Pyk2 to mediate the above responses cannot be excluded.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Given the involvement of Pyk2 and its downstream kinase c-Src in activating RhoA/ ROCK pathway (19,45,46), it is possible that Pyk2 promotes nuclear translocation and, consequently, DNA binding of RelA/ p65 by causing alterations in the actin cytoskeleton. Consistent with this possibility, inhibition of Pyk2 by tyrphostin A9 attenuates thrombin-induced Ser3 phosphorylation and, thereby, inactivation of cofilin1 (K.M.B., unpublished results), an actin-binding protein that occupies a central position in Rho-actin pathway mediating RelA/p65 nuclear translocation (43). However, in view of the reports that Pyk2 can also function downstream of RhoA/ROCK (47,48), the other possibility that RhoA/ROCK engages Pyk2 to mediate the above responses cannot be excluded.…”
Section: Discussionsupporting
confidence: 48%
“…These results suggest that Pyk2 may also be involved in facilitating the translocation of released RelA/ p65 to the nucleus. We recently found that dynamic changes in actin cytoskeleton induced by thrombin via RhoA/Rho-associated kinase (ROCK)/Cofilin pathway are necessary for nuclear translocation of RelA/p65 (43,44). Given the involvement of Pyk2 and its downstream kinase c-Src in activating RhoA/ ROCK pathway (19,45,46), it is possible that Pyk2 promotes nuclear translocation and, consequently, DNA binding of RelA/ p65 by causing alterations in the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because NF-jB response elements are present in the promoters of TNF-a, IL-6, MCP-1, and ICAM-1 genes in the inflammatory response, [39][40][41] and ripasudil significantly inhibits the levels of these proinflammatory cytokines, it is reasonable to postulate that ripasudil regulates the expression of these proteins by inhibiting NF-jB activation. Several previous studies have reported that ROCK inhibition suppressed LPSinduced activation of NF-jB in several cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…39,72,74). In addition, actin cytoskeleton polymerization has been implicated in the transport of transcription factors to the nucleus (26). Actin cytoskeleton dynamics are regulated by many signaling pathways.…”
Section: Ch-induced Nfatc3 Activation Requires Et-1 and Rokmentioning
confidence: 99%